Dynamics of Large-Scale Solar-Wind Streams Obtained by the Double Superposed Epoch Analysis: 5. Influence of the Solar Activity Decrease - Yuri I. Yermolaev; Irina G. Lodkina; Alexander A. Khokhlachev; Michael Yu. Yermolaev; Maria O. Riazantseva; Liudmila S. Rakhmanova; Natalia L. Borodkova; Olga V. Sapunova; Anastasiia V. Moskaleva (Universe, 2022)
In solar cycles 23–24, solar activity noticeably decreased and, as a result, solar wind parameters decreased. Based on the measurements of the OMNI base for the period 1976–2019, the time profiles of the main solar wind parameters and magnetospheric indices for the main interplanetary drivers of magnetospheric disturbances (solar wind types CIR. Sheath, ejecta and MC) are studied using the double superposed epoch method. The main task of the research is to compare time profiles for the epoch of high solar activity at 21–22 SC and the epoch of low activity at 23–24 SC. The following results were obtained. (1) The analysis did not show a statistically significant change in driver durations during the epoch of minimum. (2) The time profiles of all parameters for all types of SW in the epoch of low activity have the same shape as in the epoch of high activity, but locate at lower values of the parameters. (3) In CIR events, the longitude angle of the solar wind flow has a characteristic S shape; but in the epoch of low activity, it varies in a larger range than in the previous epoch.